Teleworking: A New Method for Organizing Work - Urdarević, Bojan P. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Summary: Recently, especially with the development of information technologies, the so-called flexible employment modes is increasingly represented. From the employer standpoint, this employment model has a lot of benefits in the form of reducing certain costs, but it is also more comfortable for an employee because there is no commuting. On the other hand, the great disadvantage of this kind of work is that it is difficult to separate private life from work obligations. The great changes in the economies and societies of the countries in the world brought about by the pandemic of infectious disease COVID-19 in 2020 and 2021 have greatly affected the world of work. The biggest change that has taken place in the world of work is the change of place of work, so instead of in the employer`s premises, employees switched to teleworking, mostly at home, especially during the state of emergency and prohibition of free movement. During that period, telework and work at home began to be used more and more often as synonyms for designating a specific way of conducting work – outside the employer`s premises. Such an unusual situation has left many countries surprised by how to help employees and employers, not only due to the lack of appropriate legal framework, but also due to the lack of resources needed for new technologies. In that sense, teleworking has proven to be a highly successful means of enabling continuity in the employer`s business, especial in times of natural disasters and pandemics, but at the same time, many legal issues related to the nature of such working regime are open. Keywords: teleworking, International Labor Organization. pandemic COVID-19, workplace.